SISTERHOOD IN ANN M. MARTIN'S BELLE TEAL - Delia Cesar Damayanti; Tri Pramesti (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2020)
A relationship called sisterhood has become an ordinary thing in society. The sisterhood docs not only happen to fellow women without blood tics but also occur between relationships across generations of which parents and children live. To examine the occurrence of sisterhood relationships by parents and children, the writer decided to do a study on a novel entitled Belle Teal by Ann M. Martin. Using qualitative method, the data are analysed descriptively. By applying feminist literary criticism the writer discusses several problem statements which include the sisterhood that occurs across generations and how sisterhood can be exposed to cross-generational relationships. From the analysis, it can be concludedthat sisterhood can occur across-generation. Mutual caring, intimacy and shared activity can enhance and expose sisterhood relationship among the perpetrators. Sisterhood also has a positive impact that can make a person have a more godly thought than before.